The Relationship Between Early Initiation Of Breastfeeding (EIB) And Exclusive Breastfeeding History With Stunting Severity Among Children Under Five At "X" Public Health Center Indragiri Hilir - M Berri Ridhoka; Dwi Noerjoedianto; Nur Aini; Annisa Putri S; Nabila Fahmiayumtari (International Journal of Health Engineering and Technology, 2026)
Stunting remains a significant chronic nutritional challenge in Indonesia. Early Initiation of Breastfeeding (EIB) and Exclusive Breastfeeding (EBF) are critical interventions that support child growth and serve as foundational strategies for stunting prevention. This study aims to investigate the relationship between a history of EIB and EBF and the severity of stunting (classified as stunted and severely stunted) among affected children under five within the catchment area of Public Health Center "X" in Indragiri Hilir Regency.An observational analytic design with a cross-sectional approach was employed, utilizing secondary data from the 2025 Stunting Audit. The study population consisted of 45 stunted children under five, selected through a total sampling technique. Data were analyzed using the Chi-Square test with a 95% confidence level (α=0,05) and the calculation of Odds Ratios (OR).The results indicated that the majority of respondents were categorized as severely stunted (66.7%), had a history of EIB (55.6%), and received EBF (55.6%). No significant correlation was found between a history of EIB and stunting severity (p=0,670; OR=1,313; 95%CI=0,373–4,616). Conversely, a significant association was observed between EBF and stunting severity (p=0,034; OR=0,250; 95%CI=0,067–0,931). These findings suggest that exclusive breastfeeding serves as a protective factor against increased stunting severity, whereas EIB did not demonstrate a significant relationship in this specific population. Consequently, enhancing EBF coverage must be prioritized as a pivotal component of stunting prevention and control programs.